Attitude of Farmers Towards Henna Cultivation in Western Rajasthan - Meena, M L; Singh, Dheeraj; Chaudhary, M K (Annals of Arid Zone, 2016)
The present study was conducted in Pali District of Rajasthan to measure the attitude of farmers towards henna (Lawsonia inermis) production technology. Out of 10 administrative blocks of Pali District, two were selected considering the extent of acreage and production under henna cultivation. The respondents were divided into three groups of small, medium and large farmers and a proportionate sample from each group was drawn randomly to have a total sample size of 180 henna growers. Data were collected by personal interview technique through suitable structured schedule. Nearly three-fourth of the farmers (74.44%) had favorable attitude toward henna production technology, followed by 13.33 and 11.22% of them who expressed most favorable and least favorable attitude, respectively. The most important statements of highest degree of attitude were ‘henna cultivation is the right step of CAZRI, KVK’ and ‘henna cultivation generates employment opportunities’. The least favorable attitude statements of ‘credit and subsidy facilities are adequate for its cultivation’. Key words: Attitude, favorable, henna production technology.